Ujaran Kebencian di Ruang Publik: Analisis Pragmatik pada Data Pusat Studi Agama dan Perdamaian (PSAP) Solo Raya - Kurniasih, Dwi (IAIN Palangka Raya, 2019)
This study aims to explain the forms of speech hate in the public space using pragmatic theory, especially acts of perlokusi speech. In addition, this research also explains the actualization of the Solo Raya Center for Religion and Peace Studies in minimizing the utterances of hatred in the public sphere. The method used in this study is descriptive qualitative. Data is obtained from hate speech monitored by PSAP for the period January-December 2017 until January-July 2018. Data is a word or sentence in the form of banners and the like with utterances of hate spread in public spaces. The results of the study show that all forms of speech if associated with pragmatic science, are all included in the category of perlocution speech acts, because they all lead to the power of one's influence or cause bad stereotypes. Based on the class of hate speech forms, the data presented is classified into several types of hate speech, namely (1) insult; (2) provocation; (3) oppression; (4) speech of crime. In addition, a forum for communication and discussion is needed to erode speeches of hatred. For example, the formation of the Solo Raya PSAP institution as a form of minimizing the utterance of hate in the public space.